ANALISIS PERBANDINGAN KINERJA FREENAS DAN NAS4FREE SEBAGAI SISTEM OPERASI JARINGAN NETWORK ATTACHED STORAGE (NAS) PADA LOCAL AREA NETWORK (LAN) - Akbar, Tajuddin; Jusak, Jusak; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
The development of computer network technology is currently growing exponentially along with the increasing users who make use of digital content in support of mobility. For that pupose, a provider requires a storage server which provides space for storing the digital content. Network Attach Storage (NAS) is a technology that is commonly used as a storage system. It considers to be cheap and easy for implementation. This is mainly because it can be implemented in the condition of minimal resources. On the other hand, this technology is mainly running on the open source operating system, like FreeNAS and NAS4Free This paper will discuss the performance comparation between FreeNAS and NAS4Free network operating system to analize the main activity of the storage servers, i.e. data transfer, file maintenance, and the network infrastucture. In this testing process, we used windows based file sharing common internet file system (CIFS). Parameter that are involved in the analysis are delay/latency, throughput, CPU usage, memory usage, file copy, file classification, duplicate files detection and file delete on 11 different file sizes. Based on the experiment, it is concluded thats FreeNAS operating system in general shows better performance compared to the NAS4Free. However the NAS4Free requires higher CPU usage compared to the NAS4Free.